1995
DOI: 10.1002/dc.2840120219
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound guided fine‐needle aspiration cytology: Diagnosis of hydatid disease of the abdomen and thorax

Abstract: Eight cases of hydatid disease of the abdomen and thorax were diagnosed by fine-needle aspiration (FNA) cytology under ultrasound guidance. The age of the patients ranged from 28 to 60 yr with a median of 34.5 yr; the male to female ratio was 2:6. None of the cases were diagnosed clinically as hydatid diseases but following ultrasonography suspicion of hydatid cyst was raised in two cases. The locations of cysts were the liver in six cases, the lung in one case, and the mediastinum in one case. FNA yielded cle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
33
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 7 publications
6
33
0
Order By: Relevance
“…was also ruled out by studying the smears for microbiological infections on special staining for fungus and acid fast bacilli. Anaphylaxis, which is a recognized complication, was not observed in the present case, as reported in earlier studies [8,9] .The patient was given a course of anti-helminthic drugs to which he responded well and his symptoms almost disappeared on follow up after about a year. The second child is doing well after surgery.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…was also ruled out by studying the smears for microbiological infections on special staining for fungus and acid fast bacilli. Anaphylaxis, which is a recognized complication, was not observed in the present case, as reported in earlier studies [8,9] .The patient was given a course of anti-helminthic drugs to which he responded well and his symptoms almost disappeared on follow up after about a year. The second child is doing well after surgery.…”
Section: Discussionsupporting
confidence: 83%
“…The finding of protoscolices, hooklets or hydatid membranes on cytosmears are the hallmarks of the diagnosis of an Echinococcus cyst. [7,8] In our first case, FNAC confirmed the diagnosis of Echinococcus and the patient was treated accordingly.…”
Section: Discussionmentioning
confidence: 62%
“…However, this risk has been overemphasized in the past as there are reports on cytological diagnosis of hydatid disease without complications. 12 It has been reported that the hooklets and scolices are better visualized on Ziehl Neelsen stain and this was our observation also. 13 Iynen et al reported an unusual case of a hydatid cyst in the supraclavicular soft tissue.…”
Section: Discussionsupporting
confidence: 83%
“…Owing to the possibility of cyst rupture, anaphylaxis and dissemination of cyst contents, percutaneous aspiration of lung cysts has been considered too risky for routine diagnostic use, although this procedure is now commonly used for the diagnosis and treatment of hepatic echinococcal cysts [4]. Several reports of this approach have shown it to be successful in patients with pulmonary hydatid disease [46,47].…”
Section: Laboratory and Special Investigationsmentioning
confidence: 99%